2022
DOI: 10.3390/su14074091
|View full text |Cite
|
Sign up to set email alerts
|

Women Entrepreneurship for Sustainability: Investigations on Status, Challenges, Drivers, and Potentials in Qatar

Abstract: Economic diversification is vital in achieving sustainable economic development. This diversification is chiefly important for countries relying on natural resources for their economy, such as Qatar. Private enterprises, mainly through small-to-medium enterprises (SMEs), have been recognized as crucial and effective means for healthy economic diversification, stimulating economic development, and ensuring equal sharing and distribution of wealth. Recognizing the vulnerabilities within the current economic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 55 publications
2
23
0
2
Order By: Relevance
“…Double-burden syndrome refers to the heavy society and family expectation of women to be fully responsible for their family and employment duties at the same time. Presently, and despite the freedom allotted to women by the religion of Islam to practice entrepreneurial activities in these labeled "patriarchal" and "conservative" societies, the prevalent cultural perception of women's contribution to the society and economy outside of their houses' boundaries is still negative in the MENA-and mainly in the GCC-region, leading to the existence of multiple cultural barriers to navigate through [62,[67][68][69][70][71]. Batool and Ullah [72] found that family support has a strong effect on women's entrepreneurial success.…”
Section: Female Entrepreneurshipmentioning
confidence: 99%
“…Double-burden syndrome refers to the heavy society and family expectation of women to be fully responsible for their family and employment duties at the same time. Presently, and despite the freedom allotted to women by the religion of Islam to practice entrepreneurial activities in these labeled "patriarchal" and "conservative" societies, the prevalent cultural perception of women's contribution to the society and economy outside of their houses' boundaries is still negative in the MENA-and mainly in the GCC-region, leading to the existence of multiple cultural barriers to navigate through [62,[67][68][69][70][71]. Batool and Ullah [72] found that family support has a strong effect on women's entrepreneurial success.…”
Section: Female Entrepreneurshipmentioning
confidence: 99%
“…Since no economy can be sustainable unless it constantly adjusts to changing conditions [1], economic diversification is vital in achieving sustainable economic development, especially for countries relying on nonrenewable natural resources, such as oil and gas, in the case of the Gulf Cooperation Council (GCC) countries [2,3]. Indeed, economic diversification is a critical component of sustainable development since it improves macroeconomic stability and fosters structural and long-term change in the economy and other development pillars such as social institutions and dimensions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Located in the Arabian Peninsula, Qatar is a small country covering an area of 11,437 km 2 and has a population of 2.723 million as of September 2020 [15]. Qatar is a small oil producer, but with 12.4% of the proven global gas reserves, it ranks third behind Russia and Iran [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O empreendedorismo por meio de pequenas e médias empresas é crucial para a diversificação econômica, estimulando a economia e garantindo uma partilha equitativa na distribuição da riqueza (Al-Qahtani et al, 2022). No entanto, é preciso reconhecer as vulnerabilidades.…”
Section: Introductionunclassified